Cu and CuO Nanoparticles in Heat Transfer Applications: A Comprehensive Review - Hani Chotai,; Rupeshkumar V. Ramani,; Jaysukh Markna,; Bharat Kataria, (Journal of Advanced Mechanical Engineering Applications, 2025)
This review highlights the role of Copper (Cu) and Copper Oxide (CuO) nanoparticles in enhancing heat transfer through mono, binary, and ternary nanofluids. Mono nanofluids consistently improved thermal conductivity, viscosity, pressure drop, and heat transfer coefficient, with higher gains at higher concentrations. Binary systems showed synergistic effects, with CuO–MWCNT yielding maximum conductivity, CuO–TiO? showing Newtonian behavior, and Cu with Al?O? and TiO? achieving peak conductivity at a 40:40:20 ratio. Ternary mixtures of Cu, CuO, and Al?O? offered further conductivity enhancement but with larger pressure drops, notably at 60:20:20. Overall, nanoparticle selection, base fluid, and mixing proportion are key to balancing thermal performance with hydrodynamic penalties.